INNV-35. ROUTINE SEQUENCING OF BRAIN TUMORS UNCOVERS HIGH RATES OF ACTIONABLE OPPORTUNITIES: THE UNC EXPERIENCE. (5th November 2018) - Khagi, Simon; Dees, E Claire; Bell, Emily; Pietrosimone, Kathryn; Garrett, Amy
Abstract: Since November 2017, the University of North Carolina (UNC) Brain Tumor Program has performed next generation sequencing (NGS) on newly diagnosed brain tumors through the Strata Trial, which uses the StrataNGS assay to evaluate genomic variants in 94 genes. Brain tumors were analyzed from 77 patients revealing 137 total molecular alterations. We defined actionable alterations as: (1) revealing potential enrollment into biomarker-driven clinical trials (regardless of histology); (2) allowing for off-label use of targeted therapy; (3) identifying occult and non-canonical alterations that lead to changes in prognosis and management. At UNC we've identified 26 brain tumors with actionable alterations (34%), and 18 brain tumors (23%) eligible for a nationally-available biomarker-driven trial. These results have provided useful data to inform feasibility of biomarker-driven clinical trials using targeted therapies to treat brain tumor patients seen at UNC. Furthermore, NGS of brain tumors has allowed us to utilize precision medicine in a population of patients with very few treatment options. In particular, we've exploited a BRAF V600E mutation to treat progressive glioblastoma (GBM) with BRAF-targeting agents. The patient rapidly responded to therapy and recovered functionality previously lost while on standard of care therapy. Additionally, NGS identified 1 GBM and 2 anaplastic astrocytoma (AA) patients with MET alterations, which are uncommon in high grade gliomas. Two of these patients enrolled in a biomarker-driven clinical trial at UNC, which would not have been possible without NGS. The patient with GBM has maintained disease control for over 6 months. Our experiences highlight the importance of routine NGS in the management of patients with brain tumors.